Status of swimming skills development among swimmers of different ages and genders - medalists at the XXXIII Olympic Games 2024, Paris, France - Ganchar, I.; Ganchar, O.; Ciorba, C.; Medynskyi, S.; Protsenko, A.; Tsybulska, V.; Kyriienko, O.; Sukhanova, H.; Potop, V. (Journal of Physical Education and Sport, 2025)
Purpose of the study: to assess the level of achievements and swimming skills development among swimmers who won medals in pool and open-water (marathon) swimming events at the xxxiii olympic games 2024, paris, france. material. a summarized overview of the official competition protocols for 19 event categories at the xxxiii olympic games 2024 in paris, france, was conducted. it included both male and female athletes (87 men and 87 women, totaling 174 participants). results. the leading countries in olympic swimming at the xxxiii olympic games paris 2024 were represented by 19 national teams: usa - 28 medals (10 men + 18 women), australia - 19 (7 + 12), china - 12 (5 + 7), canada - 8 (3 + 5), france - 7 (6 + 1), italy - 6 (5 + 1), hungary - 5 (5 + 0), great britain - 5 (5 + 0), germany - 3 (2 + 1), ireland - 3 (2 + 1), netherlands - 3 (1 + 2), sweden - 2 (0 + 2), south africa - 2 (0 + 2), romania - 2 (1 + 1), hong kong - 2 (0 + 2), greece - 1 (1 + 0), japan - 1 (1 + 0), south korea - 1 (1 + 0) and switzerland - 1 (1 + 0). the age characteristics of the medal-winning swimmers were analyzed in detail. no significant differences in age between men and women were observed in seven events. the greatest age differences were noted in nine events, where men were older by 5-6 years. conversely, in four events women were older than men by 3-6 years. the overall average age was 24.73 ± 2.38 years for men and 24.00 ± 1.78 years for women (t = 0.403, p > 0.05), indicating no statistically significant age difference between genders. regarding swimming speed, the smallest gender difference was recorded in the 10,000 m marathon event (0.11 m/s), followed by freestyle (0.12 m/s), medley (0.155 m/s), relay (0.15 m/s), breaststroke (0.16 m/s), backstroke (0.16 m/s) and butterfly (0.185 m/s). the largest difference was noticed in freestyle events, reaching 0.203 m/s. the overall average difference in swimming speed between male and female medalists was 0.16 m/s (men: 1.83 ± 0.15 m/s; women: 1.67 ± 0.14 m/s; t = 7.63, p < 0.05), which was statistically significant. the greatest gender speed disparity was observed in the 50 m sprint (0.25 m/s), followed by 100 m events (0.19 m/s), 200 m events (0.154 m/s), relay swimming (0.15 m/s), stayer events (0.128 m/s) and marathon swimming (0.11 m/s). these findings indicate a consistent trend: the shorter the distance, the greater the speed difference between genders. conclusion. the results of the xxxiii olympic games paris 2024 in pool swimming and marathon swimming events show the dominance of top nations like the usa, australia and china, with both male and female athletes performing at similarly high levels. although men outperformed women by an average of 0.16 m/s, particularly in sprint events, the gap narrows over longer distances, reflecting progress in training and competitive equity.